Solenoxyphus Reuter, 1875 (Hemiptera: Heteroptera: Miridae: Phylinae): revised diagnosis, a new species and new generic synonym - Konstantinov, Fedor V.; Korzeev, Andrei I. (Zootaxa, 2014)
Solenoxyphus kazakhstanicus sp. n. is described from the vicinity of Dzhezkazgan, Western Kazakhstan. The generic name Voruchia Reuter, 1879 is synonymized with Solenoxyphus Reuter, 1875. Illustrations of the male and female genitalia, photographs of the dorsal habitus, host, and distributional records are given for the new species and S. vittiger comb. nov., the type species of Voruchia. Female genitalia of Solenoxyphus and Boopidocoris spp. are studied for the first time and an updated generic diagnosis of the former genus is provided. The placement of both genera within the tribe Nasocorini sensu Schuh & Menard (2013) is briefly discussed.